How Innovative Behavior Affects Lecturers’ Task Performance: A Mediation Perspective - Adolf Bastian; Widodo Widodo (Emerging Science Journal, 2022)
Objectives: Task performance is an essential determinant of organization life, including profit and non-profit organizations. Lecturers' task performance in universities is vital to realizing the goals, which include creating quality graduates and building competitiveness that promises sustainable progress for all involved stakeholders. Therefore, it is crucial to investigate lecturers' task performance by considering other relevant variables. Accordingly, this study examined Indonesian lecturers' task performance based on innovative behavior, job involvement, and organizational citizenship behavior (OCB). The study also attempted to find relevant models of innovative behavior influencing lecturers' task performance, mediated by job involvement and OCB. Methods: Questionnaires with the Likert scale were used to collect data from 230 lecturers selected using accidental sampling. The data were analyzed using descriptive and correlational techniques and structural equation modeling. Results: Innovative behavior, job involvement, and OCB significantly affected the lecturers' task performance. Besides, job involvement and OCB mediating innovative behavior affected the lecturers' task performance. However, the mediating role of job involvement was more prominent than that of OCB. Novelty: A new model of innovative behavior mediated by job involvement and OCB was developed, affecting lecturers’ task performance. It is hoped that the model can trigger interesting discussions and raise new hope for task performance improvement based on innovative behavior mediating job involvement and OCB. Doi: 10.28991/ESJ-2022-SIED-09 Full Text: PDF